Public Health Has an Equity Problem: A Latinx's Voice - Jesus Ramirez-Valles (Frontiers Media S.A., 2020)
Public health has an equity problem. One of the main pillars of our public health system, schools and academic programs of public health, are under the control of white (heterosexual) faculty. They continue to exclude brown, black, and indigenous people from their faculty and leadership ranks. This racism pervades institutional policies and culture and is a major fault in the quest for health equity. In this essay, I center on the experience of Latinx faculty to examine the roots of this inequity and the arguments for diversity and inclusion. I also propose avenues for change and argue for institutional transformation that goes beyond adding people of color to faculty and leadership roles.